Intercellular coupling through gap junctions masks M cells in the human heart - Conrath, C (Cardiovascular research, 2004)
M cells have been described in many mammalian species. They are thought to be relevant for the genesis of long QT intervals, afterdepolarizations and for dispersion in action potential duration and in repolarization time. Their role in the human heart is subject to debate. We simulated action potential propagation in a strand of transversally oriented myocytes running from endocardium towards epicardium through the left ventricular free wall. The characteristics of the myocytes were either based on the Priebe-Beuckelmann ventricular cell model or on the Luo-Rudy ventricular cell model. The former model is based on the latter and includes adaptations in order to mimic the human ventricular myocyte. The amount and location of M cells as well as the intercellular coupling through gap junctions were varied. Also, we assessed action potential duration in a Langendorff-perfused explanted human heart and in a wedge preparation obtained from such a heart. At low, but physiological intercellular coupling conductance, the inclusion of M cells leads to a much longer 'QT interval' in the simulations than in the in vivo or isolated human heart. Dispersion in repolarization time becomes unphysiologically large when M cells are included in the strand and is also substantially larger than in the in vivo or isolated human heart. At stronger intercellular coupling this effect disappears. The manifestation of M cells is absent in the human heart, probably by effective intercellular coupling, turning them functionally "invisible".